Incentives for Quality over Time – The Case of Facebook Applications - Jörg Claussen; Tobias Kretschmer; Philip Mayrhofer (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2011)
We study the market for applications on Facebook, the dominant platform for social networking and make use of a rule change by Facebook by which high-quality applications were rewarded with further opportunities to engage users. We find that the change led to quality being a more important driver of usage while sheer network size became less important. Further, we find that update frequency helps applications maintain higher usage, while generally usage of Facebook applications declines less rapidly with age.
urn:nbn:de:bvb:19-epub-12500-1
Keywords: 650